Using photography to enhance GP trainees' reflective practice and professional development. Issue 3 (8th February 2018) - Rutherford,; Forde, Emer; Priego-Hernandez, Jacqueline; Butcher, Aurelia; Wedderburn, Clare
Abstract : The capacity and the commitment to reflect are integral to the practice of medicine and are core components of most general practitioners (GP) training programmes. Teaching through the humanities is a growing area within medical education, but one which is often considered a voluntary 'add-on' for the interested doctor. This article describes an evaluation of a highly innovative pedagogical project which used photography as a means to enhance GP trainees' reflective capacity, self-awareness and professional development. Photography was used as a tool to develop GP trainees' skills in recognising and articulating the attitudes, feelings and values that might impact on their clinical work and to enhance their confidence in their ability to deal with these concerns/issues. We submit that photography is uniquely well suited for facilitating insight and self-reflection because it provides the ability to record 'at the touch of a button' those scenes and images to which our attention is intuitively drawn without the need for—or the interference of—conscious decisions. This allows us the opportunity to reflect later on the reasons for our intuitive attraction to these scenes. These photography workshops were a compulsory part of the GP training programme and, despite the participants' traditional scientific backgrounds, the results clearly demonstrate the willingness of participants to accept—even embrace—the use of art as a tool for learning. The GP trainees who took part in this project acknowledged it to be beneficial for both their personal and professional development.